Characterization of Microcystis (Cyanobacteria) Genotypes Based on the Internal Transcribed Spacer Region of rRNA by Next-Generation Sequencing - Huo, Da; Chen, Youxin; Zheng, Tao; Liu, Xiang; Zhang, Xinyue; Yu, Gongliang; Qiao, Zhiyi; Li, Renhui (Frontiers in Microbiology, 2018)
Microcystis is one of the most common and dominant bloom-forming cyanobacteria in freshwater worldwide. The method for genotype detection based on traditional molecular cloning is expensive and time consuming and generates a limited number of sequences. In this study, a high-throughput sequencing (HTS) method was developed to detect the internal transcribed spacer (ITS) regions between 16S to 23S rRNA region of Microcystis populations along a typical water system in Yuqiao Reservoir–Haihe River in Tianjin, northern China. A total of 629,341 reads were obtained and clustered into 2005 Operational Taxonomic Units (OTUs). Analysis of alpha diversity indices showed that the Haihe River is more diverse than Yuqiao Reservoir. In general, the two water areas exhibit a clear differentiation pattern in OTU abundance, sharing genotypes from a small part of Yuqiao Reservoir with those in the Haihe River. Phylogenetic analysis further indicated the possible flexible evolution of Microcystis genotypes occurring in the research areas. This study provides the first exhaustive description of HTS method for detection of ITS region to evaluate Microcystis intra-species diversity and relationship.